(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Hormone replacement therapy (estrogens with or without progestogens) is widely used medication therapy worldwide for alleviating post menopausal symptoms. The association of Hormone replacement therapy (HRT) and risk of cancers leads to many studies. A lot of controversial results regarding the risk of cancers arises which leads to many questions that are still unanswered and can be cleared by further extensive research. There is considerable uncertainty among general practitioners to balance the beneficial and harmful effects of long term HRT particularly regarding the risk of cancers (breast, ovarian, endometrial, colorectal, lung cancers, lymphoma’s and leukaemia’s). The goal of HRT is not only to normalize the follicle stimulating hormone value, but rather to use the minimum effective dosage to suppress vasomotor reactions, treat urogenital atrophy, prevent trabecular and cortical bone loss, and reduce cardiac risk. Use of HRT should be individualized for risks and benefits of each patient that is being taken into consideration.